Needs Analysis for Canva and Heyzine-Based Interactive Digital Flipbook Teaching Materials to Enhance Students' Creative Thinking Skills in History Learning - Farhan Nur Ghifari; Erlina Wiyanarti (Universitas Hamzanwadi, 2026)
History learning in the 21st century requires innovative, technology-based learning media to foster students' creative thinking skills. However, history instruction in schools remains predominantly teacher-centered, relying on lectures and printed textbooks, which limits students' opportunities to develop their creativity. This study aimed to analyze the need to develop interactive digital flipbook teaching materials using Canva and Heyzine on the topic of humans in space and time to improve senior high school students' creative thinking skills. This research employed a descriptive qualitative approach involving 31 tenth-grade students and one history teacher at a senior high school in Lebak Regency, Banten. Data were collected through classroom observations, teacher interviews, and student needs questionnaires. The findings indicate that students highly expect learning media containing videos (61.3%), interactive digital flipbooks (61.3%), animations and audio (58.1%), while classroom instruction remains dominated by lectures and government-issued printed textbooks (71%). Interview results revealed that although the school has adequate digital facilities, the use of interactive teaching materials has not been optimized, and teachers require alternative media to overcome the limited availability of printed textbooks. These findings suggest that developing Canva- and Heyzine-based interactive flipbooks is highly relevant to support more engaging, student-centered, and contextual history learning. Integrating text, images, audio, video, and animation in a single platform is expected to facilitate the development of students' creative thinking skills, including fluency, flexibility, elaboration, and originality, while addressing the challenges of history education in the digital era.